2021
DOI: 10.3390/toxins13110777
|View full text |Cite
|
Sign up to set email alerts
|

Natural Occurrence of Deoxynivalenol in Cereal-Based Baby Foods for Infants from Western Poland

Abstract: The study examined 110 samples of baby products based on rice, wheat, maize and multi-grains available on the western Polish market in order to detect the level of deoxynivalenol (DON) by means of HPLC (high-performance liquid chromatography) with a fluorescence detector (HPLC-FLD). DON was detected in 9.09% of the infant food samples, with an average and maximum level of 107.8 ± 30 and 148 μg/kg, respectively. The highest concentration of DON was detected in food for infants: wheat-based (mean 121 ± 7.07, 4.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The high incidence of DON in cereal-based complementary foods has also been reported in Wang et al’s study [ 32 ]. Compared with the survey that has been conducted in other countries, the positive rate of DON in the infant food samples that were collected in this study was much higher (60.7% versus 9.09%) [ 36 ]. This is considered to be possibly related to the current status that China has not implemented the DON limit standard for cereal-based complementary foods for infants, and many excipients are added to cereal-based complementary food products during the production process.…”
Section: Discussionmentioning
confidence: 66%
“…The high incidence of DON in cereal-based complementary foods has also been reported in Wang et al’s study [ 32 ]. Compared with the survey that has been conducted in other countries, the positive rate of DON in the infant food samples that were collected in this study was much higher (60.7% versus 9.09%) [ 36 ]. This is considered to be possibly related to the current status that China has not implemented the DON limit standard for cereal-based complementary foods for infants, and many excipients are added to cereal-based complementary food products during the production process.…”
Section: Discussionmentioning
confidence: 66%
“…From 2014 to 2021, thirteen studies reported the presence of mycotoxins in cereal-based infants’/children’s food products in Europe. The majority of the studies verified that TCs, particularly DON, are the most prevalent mycotoxins [ 42 , 43 , 44 , 47 , 48 , 50 , 51 , 54 ]. In some of these studies, DON levels were above the maximum limit established by EC (200 µg/kg) [ 42 , 43 , 48 , 50 ].…”
Section: Major Mycotoxins In Cerealsmentioning
confidence: 99%
“…It is also possible to see some distinctions between cereal-based food products for babies, for infants, and for children, as with different age groups there are different nutritional needs, different eating habits, and different susceptibilities. Some studies [ 48 , 50 , 54 ] clearly present their results with a separation of these types of products, where the first team divided their samples into infant cereals and breakfast cereals [ 48 ], the second team considered two types of samples, gluten-free samples for babies from 4 to 6 months of age and multi-cereals for infants aged 7 to 12 months [ 50 ], and the last team separated their samples by brand, type of cereal, and consumption age [ 54 ].…”
Section: Gaps In the Research Of Mycotoxins In Infant/children Cereal...mentioning
confidence: 99%
“…A survey of 13,629 samples from 77 countries around the world showed that the pollution rates for each continent were as follows: North America, 67%; South and Central America, 67%; Europe, 63%; Asia, 80%; the Middle East, 65%, and Africa, 75%, suggesting regular human exposure [ 3 ]. Global scientists pay attention to DON and its derivatives because of their high contaminated rates and significant deleterious effects on humans and animals [ 2 , 4 ], and the fact that risk assessments by food safety authorities reported exposure to potentially exceed established health-based guidance values for parts of the population [ 5 , 6 ]. The occurrence of DON was observed in 450 wheat samples collected during 2013–2015 in Jiangsu province, China.…”
Section: Introductionmentioning
confidence: 99%